On Weathering: Anti-Imperialist Solidarity Struggles Around the Nicaragua Mural in Berlin After 2018 (Alternautas, 2024)
This article looks at the process of historical reinterpretation and anti-imperialist struggle around the Nicaragua mural in (former East) Berlin to demonstrate how internationalist solidarity does not unfold singularly but in a multi-layered, often contradictory manner. Since 2018, this mural has turned from an inconspicuous site into a place of contestation. On the one hand, for residents, the mural has transformed into a projection of rescuing and reinstating memory of the former GDR’s efforts of internationalist friendship and solidarity. On the other hand, it has become a site for political struggle for Nicaraguan exiles living in the area. Based on 14 months of ethnographic fieldwork and archival research in Nicaragua and Germany in 2018–2019 and 2023, this article complicates how memory practices shape everyday lives in Berlin for German and Nicaraguan residents alike. Their divergent interpretations of the mural’s meaning sheds light on the tensions of memory politics vis à vis political and historical reinterpretation and demonstrate the potential for the Nicaragua mural to place a magnifying glass over the anti-imperial politics of Berlin.